INTERAKSI GENETIK X LINGKUNGAN UNTUK KETAHANAN CABAI ( Capsicum annuum L.) TERHADAP ANTRAKNOSA YANG DISEBABKAN OLEH Colletotrichum acutatum - Muhammad Syukur; Sriani Sujiprihati; Jajah Koswara; Widodo . (Universitas Pekalongan, 2010)
Appearance of a plant is determined by genetic factors, environmental factors and interactions between them. The genetic x environment interactions become an important concern for breeders, in addition to genetic factors. Purpose of this study was to examine the genetic x environment interactions for resistance of pepper to anthracnose. Materials used were 16 hybrids that were planted at three locations. Complete randomized block design (RCBD) was used with three replications. Replicates nested within location. Twenty of hot pepper that has been worn but is still green from each replication was inoculated with C. acutatum, PYK 04 isolate. Disease incidence was observed five days after inoculation. The results showed that the genotype x location interaction was significant different to resistance resistance caused by Colletotrichum acutatum PYK 04 isolate. Pepper genotypes stable in anthracnose resistant character in three selection environments was IPB CH3, IPB CH6, and IPB CH25. The genotypes were suitable for selection environment Ciherang, Leuwikopo and Tajur. Genotype IPB CH50 and IPB CH51 were suitable for selection environment Tajur. Imperial genotypes was suitable for the environment selection Ciherang. IPB CH5 and IPB CH4 CH5 were suitable for Lewikopo environment.Keywords:genetic x environmental interaction, anthracnose, resistance, pepper, Colletotrichum acutatum